2018
DOI: 10.3390/ijms19124086
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Synthetic Flavone Derivatives on Pan-Aurora Kinases: Induction of G2/M Cell-Cycle Arrest and Apoptosis in HCT116 Human Colon Cancer Cells

Abstract: Members of the aurora kinase family are Ser/Thr kinases involved in regulating mitosis. Multiple promising clinical trials to target aurora kinases are in development. To discover flavones showing growth inhibitory effects on cancer cells, 36 flavone derivatives were prepared, and their cytotoxicity was measured using a long-term clonogenic survival assay. Their half-maximal growth inhibitory effects against HCT116 human colon cancer cells were observed at the sub-micromolar level. Pharmacophores were derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Flavones are commonly found in many fruits and plant foods [21]. The main flavones are apigenin, luteolin and diosmetin which showed potent inhibitory effects on the proliferation, activation of apoptosis and cell cycle regulation, but also invasion and metastasis [21].…”
Section: Anticancer Effects Of Flavonoids In Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Flavones are commonly found in many fruits and plant foods [21]. The main flavones are apigenin, luteolin and diosmetin which showed potent inhibitory effects on the proliferation, activation of apoptosis and cell cycle regulation, but also invasion and metastasis [21].…”
Section: Anticancer Effects Of Flavonoids In Lung Cancermentioning
confidence: 99%
“…Flavones are commonly found in many fruits and plant foods [21]. The main flavones are apigenin, luteolin and diosmetin which showed potent inhibitory effects on the proliferation, activation of apoptosis and cell cycle regulation, but also invasion and metastasis [21]. Dietary flavones may serve as preventive/therapeutic agents against different human cancers due to their interfering capacity with epigenetic pathways [22].…”
Section: Anticancer Effects Of Flavonoids In Lung Cancermentioning
confidence: 99%
“…From the chemical structure of platycodin D and platycoside E, it can be predicted that there are enzymes which can catalyze degradation of glycosyl group from PE to PD. Two extracellular experiments showed that β-D-glucosidase from Aspergillus usamii and Caldicellulosiruptor bescii can successfully catalyze conversion of PE and platycodin D3 into PD under optimal reactions conditions 18 , 19 . In this study we attempt to find out appropriate candidate genes encoding enzymes involving in conversion of PE, platycodin D3 into PD in traditional Chinese medicinal plant P. grandiflorus .…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional structure of IκB kinaseβ (IKKβ) was adopted from a protein data bank deposited as 4KIK.pdb [40]. The detailed experimental procedures followed to the methods previously reported [41].…”
Section: In Silico Docking With Iκb Kinaseβ (Ikkβ)mentioning
confidence: 99%